The influence of the internal control system, financial statement audit, management of village fund allocation, and implementation of good governance on the quality of financial statements of the sei kepayang tengah asahan village office - Marpaung, Tuah Rizky; Nurwani, Nurwani; Syafina, Laylan (Institute of Computer Science (IOCS), 2025)
This research aims to see the influence of the internal control system, financial report audits, management of village fund allocations, and the implementation of good governance on the quality of financial reports of the Sei Kepayang Tengah Asahan village office. The population in this study were all auditors at the Sei Kepayang Tengah Asahan village office, and the sample in this study was thirty auditors at the Sei Kepayang Tengah Asahan village office. The data used in this research is primary data, namely using an instrument in the form of a questionnaire. The results obtained in this research show that the internal control system, audit of financial reports, management of village fund allocations, and implementation of good governance have positif and significant effect on the quality of financial reports, meaning that the implementation of an internal control system, audit of financial reports, good management of village fund allocations and maximum implementation of good governance will produce quality financial reports